Supraclavicular versus infraclavicular approach in inserting totally implantable central venous access for cancer therapy: A comparative retrospective study - Souadka, Amine; Essangri, Hajar; Boualaoui, Imad; Ghannam, Abdelilah; Benkabbou, Amine; Amrani, Laila; Mohsine, Raouf; Majbar, Mohammed Anass (PloS one, 2020)
The insertion of an implantable central venous access is performed according to a variety of approaches which allow the access to the subclavian vein, yet the supraclavicular technique has been underused and never compared to the other methods. The aim of this study was to testify on the efficacy and safety of the subclavian puncture without ultrasound guidance « Yoffa » in comparison with the classical infraclavicular approach (ICA). This is a retrospective study with prospective data collection on patients followed at the national oncology institute for cancer, in the period extending from May 1st 2017 to August 31st 2017. All patients had a totally implantable central venous access device inserted by the same surgeon AS for chemotherapy administration and demographic characteristics, as well as procedure details were examined. The primary outcomes were the intraoperative complications, while the secondary outcomes represented immediate postoperative and mid-term complications (at 15 months of follow up). Outcomes were compared between techniques by means of non parametric tests and the Fischer test. Our study included 135 patients with 70 patients undergoing the subclavian technique, while 65 were subject to the infraclavicular approach. Both groups had no statistically significant demographic characteristics. The number of vein puncture attempts exceeding once, the accidental artery puncture and operative time were more significant in the ICA group; (39,6 vs 17,6 p = 0,01) (9.2% vs 0; p = 0,01) and (27± 13 vs 23± 8min, p = 0.045) respectively. There was no statistically significant difference in the immediate and midterm complication rate between the two methods 1(1,4) vs 2 (3) p = 0.5. In case of unavailability of ultrasonographic guidance, the use of the supra-clavicular landmarks approach is linked to higher success rates and less arterial punctures, thereby proving to be a safe and reliable approach.